(3GdZQjH GdeUfas - (3GdbGSe Hf SdGe GdgQhj GdCROj GdNRGYj, CHh YHjO, J (B224 (3g` s
(3ChdgG (B:s
(3bGd CHh YHjO ai MOjK GdfHi Ydjg GdSdGe (B( (3ZPG CHdZ GdeGA adJjf jMed fLjSkG (B) (3bhdg adJjf jYfi efgPg GdMHGH GdYcGe s
(3BNQgG (B:s
(3hCeG eG jSJNjeg agi GdVZjfI hGdYOGhI BNQ GdcJGH s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B176 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B101s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1209s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdMOjK h GdeUWdMs